IMPROVING STUDENTS LEARNING OUTCOMES THROUGH READING SKILLS USING PICTURE MEDIA FOR ELEMENTARY SCHOOL STUDENTS - Dio Barrabas; Agung Setyawan (Citra Dharma Cindekia, 2022)
The background of this research is the lack of reading skills in grade I students of SDN Jatiwates 2. This research is a type of classroom action research using the Kurt Lewin model which consists of four stages, namely planning, implementation, observation, and reflection. The methods used to collect data are tests, observations, and documentation. The collected data was then analyzed through qualitative and quantitative descriptive approaches. The results obtained in this study are learning by using image media as learning media is welcomed by students. Students at SDN Jatiwates 2 experienced an increase in learning related to reading skills in this way of learning from the pre-cycle stage to the second cycle. Based on the results of the research above, it can be concluded that learning using image media using the SAS method can be used as an alternative in reading skills and can be applied in elementary schools.